The role of psychological correction in discogenic dorsopathies treatment - N. Chuhraev; W. Zukow; N. Samosiuk; О. Danilova (Kazimierz Wielki University, 2017)
Chuhraev N., Zukow W., Samosiuk N., Danilova О. The role of psychological correction in discogenic dorsopathies treatment. Journal of Education, Health and Sport. 2016;6(11):262-270. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.166568 http://ojs.ukw.edu.pl/index.php/johs/article/view/3995       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 01.11.2016. Revised 12.11.2016. Accepted: 13.11.2016.       UDC 615.8   THE ROLE OF PSYCHOLOGICAL CORRECTION IN DISCOGENIC DORSOPATHIES TREATMENT   Chuhraev N.1, Zukow W.2, Samosiuk N.3, Danilova О.4   1. LLC «NMZ Мedintech», Kiev, Ukraine. Email: nv11111@mail.ru 2. Kazimierz Wielki University, Bydgoszcz, Poland 3. National Medical Academy of Postgraduate Education named P. L. Shupik, Department of neurology №1, Kiev, Ukraine 4. Private higher education institution «Interregional Academy of Personnel Management», Kiev, Ukraine     Summary   The article dials with the role of psychological correction in the treatment of discogenic dorsopathies based on zonal applicated ultraphonophoresis of analgesic drugs and psychological treatment of anxious depression (F41.2 Mixed anxiety and depressive disorder) with the use of binaural rhythms and magnetofotostimulation.     Keywords: discogenic dorsopathy, anxious depression, binaural rhythms, magnetofotostimulation.